(untitled) (Eurasian Research Bulletin, 2024)
The article illustrates the issues of teaching English to students of nonlinguistic universities. Due to the fact that the development of communicative competencies is becoming one of the important aspects, education is carried out with a pragmatic approach, including a methodology that offers a solution to the problem in the close relationship of grammar, selection of vocabulary and the use of technical means.